Employee Performance Analysis Of Workload And Work Stress In Hospital Ibnu Sina Makassar City - Ulyana Muslimin; Pandi Putra (Jurnal Mirai Management, 2022)
Abstrak This study aims to determine (1) the effect of workload and work stress partially on the performance of cleaning service employees at Ibnu sina Makassar Hospital, (2) the effect of workload and work stress simultaneously on the performance of cleaning service employees at Ibnu sina Makassar Hospital in the case of this research is a cleaning service employee of Ibnu sina Makassar Hospital. This research is a quantitative research. This study uses primary data, which is obtained by distributing questionnaires directly at Ibnu sina Makassar Hospital. The population in this study were 30 employees of the Ibnu sina Makassar Hospital cleaning service. Samples were taken as many as 30 respondents using the saturated sample technique. The data obtained was then processed using the SPSS Statistics 22 tool. The results showed that (1) workload (X1) had no effect ( 1.366 ) and was significant ( 0.183 > 0 , 05) on the performance of Ibnu sina Makassar Hospital employees, (2) work stress (X2) had no effect ( 1,981 ) and significant (0 , 0 58 > 0 , 05) on the performance of Ibnu sina Makassar Hospital employees, (3) workload and work stress have a significant effect (0.0 13 > 0.05) simultaneously on the employee performance of Ibnu sina Makassar Hospital. Kata Kunci: Workload, Work Stress, and Performance